How do I manage severe postpartum hemorrhage?. Issue 5 (22nd April 2020) - Butwick, Alexander; Lyell, Deirdre; Goodnough, Lawrence
Abstract : In the United States, postpartum hemorrhage (PPH) accounts for 4.6% of all maternal deaths and is responsible for major peripartum medical and surgical morbidity. Therefore, a national health priority is to ensure that women who experience severe PPH receive timely, appropriate, and effective treatment. In this article, we describe our system‐wide approach for the planning and delivery of women with suspected placenta accreta spectrum disorder, a condition associated with life‐threatening blood loss at the time of delivery. We also highlight current evidence related to transfusion decision making and hemostatic monitoring during active postpartum bleeding. Specifically, we describe how we activate and use the massive transfusion protocol to obtain sufficient volumes and types of blood products. We also describe how we use viscoelastic monitoring (thromboelastography) and standard laboratory tests to assess the maternal coagulation profile. Finally, we review the findings of recent studies examining the potential efficacy of tranexamic acid and fibrinogen concentrate as adjuncts for PPH prevention and treatment. We describe how we have incorporated these drugs into PPH treatment protocols at our institution.